1977
DOI: 10.1104/pp.60.3.422
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Subunit Structure of Protochlorophyllide Holochrome by Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis

Abstract: The subunit structue of protochlorophyllide holochrome (PCH) and chlorophyllide holochrome (CH) In this paper we examine the subunit structure of PCH purified from dark-grown bean leaves. The fate of the pigmentprotein complex after photoreduction and after the completion of the dark spectroscopic shift (22) MATERIALS AND METHODS PREPARATION OF HOLOCHROMEBean seedlings (Phaseolus vulgaris var. red kidney) were grown on vermiculite 12 + 2 days in the dark at 22 C. The leaves (50-lOOg) were harvested and grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1979
1979
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…This was prompted by the fact that Sauer and co-workers (Alscher et al, 1976;Canaani & Sauer, 1977) claimed to have identified a cytoplasmically synthesized 15 000-mol.wt. pigment-binding peptide that forms a part of the 'holochrome' unit and that after illumination becomes incorporated along with the associated pigment into the thylakoid membrane.…”
Section: Discussionmentioning
confidence: 99%
“…This was prompted by the fact that Sauer and co-workers (Alscher et al, 1976;Canaani & Sauer, 1977) claimed to have identified a cytoplasmically synthesized 15 000-mol.wt. pigment-binding peptide that forms a part of the 'holochrome' unit and that after illumination becomes incorporated along with the associated pigment into the thylakoid membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Because the protein is membrane-associated, most attempts to purify the pigment-protein complexes used detergent solubilization of etioplast membranes as the first step. Depending on the procedure used to solubilize the etioplast internal membranes, holochromes with molecular weight (MW) ranging from 45 to approximately 600 kDa were obtained (29)(30)(31)(32). Although Pchlide holochrome retains photochemical activity, it exhibits spectral properties that strongly differ from those of photoactive Pchlide in situ.…”
Section: Isolation Of Pchlide-lpor Complexesmentioning
confidence: 99%
“…The molecular weights of the photoconvertible PChl complex and the Chlg,, complex were determined as c. 600,000. In contrast, the apparent molecular weight of the Chlg74 complex is less than 70,000 (Canaani and Sauer 1977). A decrease in the molecular weight of the subunits of the Chl complex after completion of the spectral shift has also been observed (Canaani and Sauer 1977).…”
Section: Introduetionmentioning
confidence: 97%
“…PChl holochrome has also been isolated from etiolated bean leaves using Triton X-100 (Schopfer andSiegelman 1968, Canaani andSauer 1977). Immediately after photoconversion the absorption maximum of Chl is at c. 678 nm, and it shifts slowly to 672 to 674 nm (Schopfer andSiegelman 1968, Canaani andSauer 1977). The molecular weights of the photoconvertible PChl complex and the Chlg,, complex were determined as c. 600,000.…”
Section: Introduetionmentioning
confidence: 99%